the composition of functions gives:
g(f(0)) = -6
Here we have the two functions:
f(x) = 3(x - 7)/4
g(x) = 2x - 1
The problem in the answer is in the third step, where the distribution is done incorrectly.
g(f(x)) = 3*( (2x - 1) - 7)/4
g(f(x)) = 3*( 2x - 8)/4
g(f(x)) = ( 6x - 24)/4
Evaluating in x = 0 we get:
g(f(0)) = ( 6*0 - 24)/4 = -24/4 = -6
That is the solution of the composition of functions.
If you want to learn more about composition of functions:
https://brainly.com/question/10687170
#SPJ1